Effect of financial reform and fiscal decentralization In Bone, Indonesia - WALINONO, A.I.; KADIR, A.R.; ANWAR, A.I. (Utopía y Praxis Latinoamericana, 2021)
ABSTRACT This paper aims to discuss the Effect of Financial Reform and Fiscal Decentralization on Financial Governance in Bone, Indonesia. Financial performance analysis can be done by looking at the ratio of the degree of fiscal decentralization, regional financial dependence, regional independence, the effectiveness and efficiency of ROI, and compatibility of direct spending to analyze the effect of financial performance on the Human Development Index (HDI). This research found that the HDI in Bone Regency 2010-2019 was influenced by the direct expenditure compatibility ratio. RESUMEN Este documento tiene como objetivo discutir el efecto de la reforma financiera y la descentralización fiscal en la gobernanza financiera en Bone, Indonesia. El análisis del desempeño financiero se puede hacer observando la relación entre el grado de descentralización fiscal, la dependencia financiera regional, la independencia regional, la efectividad y eficiencia del ROI y la compatibilidad del gasto directo para analizar el efecto del desempeño financiero en el Índice de desarrollo (IDH). Esta investigación encontró que el IDH en Bone Regency 2010-2019 estuvo influenciado por el índice de compatibilidad del gasto directo.